Pengaruh Literasi Keuangan, Keamanan Transaksi, dan Kemudahan Pengguna terhadap Keputusan Penggunaan QRIS pada Siswa Jurusan Bisnis Ritel SMK Negeri 14 Jakarta - Chika Oktapiani; Nadya Fadillah Fidhyallah; Kusworo Kusworo (Indo Publishing, 2026)
This study aims to analyze the influence of financial literacy, transaction security, and user convenience on the decision to use QRIS among retail business students at SMK Negeri 14 Jakarta. This study uses a quantitative approach with associative research type. Data were obtained from questionnaires distributed to retail business students at SMK Negeri 14 Jakarta using non-probability sampling with purposive sampling approach. Data were processed using multiple linear regression analysis with SPSS. The results show that financial literacy and user convenience have a positive and significant effect on the decision to use QRIS. Meanwhile, transaction security has no significant effect on the decision to use QRIS. In addition, financial literacy, transaction security, and user convenience simultaneously affect the decision to use QRIS. These findings indicate that the decision to use QRIS among students is influenced by understanding of financial literacy and perceived user convenience. This research is expected to be a consideration for schools and related parties in improving digital payment methods among students.